Design and implementation of application programming interface for Internet of things cloud. Issue 3 (27th June 2016) - Hou, Lu; Zhao, Shaohang; Li, Xing; Chatzimisios, Periklis; Zheng, Kan; Batalla, Jordi Mongay; Mastorakis, George; Mavromoustakis, Constandinos X.
Summary: Internet of things (IoT) technologies have developed rapidly to provide various applications and services, which benefit much on both industrial production and human lives. Meanwhile, with the deployment of cloud computing, the requirements of computing and storage capabilities of IoT can be well supported. The well‐designed application programming interfaces (APIs) are needed to offer good services of IoT cloud. APIs serve as the endpoints of services and offer convenient ways for either developers to design applications or vendors/OEMs to manufacture devices. In this paper, the design and implementation of APIs for IoT cloud is presented in detail. Taking the large number of resource‐constrained IoT devices into account, we propose the different kinds of APIs with different application protocols. APIs offer integrations between server‐side applications and client‐side applications or devices; thus, the specific implementation of APIs on these three parts are presented. Finally, a number of experiments are conducted to evaluate the performance of the designed APIs, and the result analysis is given as well. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This paper mainly describes the specific design and implementation of application programming interfaces (APIs) for Internet of Things (IoT) cloud, enabling the software developers to develop applications or vendors/OEMs to produce IoT devices that can access to IoT cloud services. In addition, performance analysis of the proposed APIs is also presented in details in this paper.